807 Diagnostic Pathways of Patients Authorized for Obstructive Sleep Apnea Testing and Treatment: A Retrospective Claims Analysis. (3rd May 2021) - Nguyen, Binh; Gordon, Aliza; Blake, Stefanida; Kalluri, Lakshmi; Chi, Winnie; Power, Thomas
Abstract: Introduction: Obstructive Sleep Apnea (OSA) has been shown to reduce health-related quality of life and is associated with cardiovascular disease and other negative health outcomes. However, many patients with suspected OSA are never tested, thereby remaining undiagnosed and untreated. In this study, we explore the diagnostic pathways and eventual treatment of individuals with suspected OSA. Methods: We conducted a retrospective, observational study, linking claims and prior authorization data of a large, geographically diverse health insurer's commercial and Medicare Advantage members. Our sample included adults with suspected OSA and no prior OSA history, whose diagnostic testing had been approved through prior authorization (N=75, 011). Using a 3-month time window following authorization, we searched for a claim to match the authorized service (home or laboratory sleep testing). We also looked for subsequent prior authorization for OSA treatment (Positive Airway Pressure (PAP) or oral appliance) and corresponding claims for those treatments within the 3-month authorization window. Results: Among the study sample (N=75, 011), 40, 002 (53.3%) had home testing only, 17, 319 (23.1%) had laboratory testing only, and 6, 053 (8.1%) had a home test followed by a laboratory test. Only 476 (0.6%) had a home test after the date of a lab test. 11, 161 individuals (14.9%) did not complete any sleep test. Of the 63, 850 individuals with any sleep testing, 39, 062 (61.2%) received prior authorization for initiating OSA treatment, and 36, 158 (92.6%) of them had a corresponding claim for treatment. Conclusion: One in eight adults with suspected OSA for whom diagnostic testing was authorized did not undergo testing; among those who tested, home testing was most common. While it is clinically appropriate to follow a negative home test with a lab test since a home test cannot rule out OSA (only confirm it), the study notes that a significant number of those with a home test require follow-up laboratory testing. Together, this represents an opportunity for reducing barriers to testing and improvement in home testing technology. Support (if any): This study was funded by Anthem, Inc.